Improving the Learning of Plate Dance Through the Explicit Instruction for Class VIII Deaf Children - Nandini Nandini; Zulmiyetri Zulmiyetri (Universitas Muhammadiyah Enrekang, 2022)
Abstract The study was conducted to see the improvement of learning the art of plate dance through an explicit instruction in class VIII deaf students at SLB N 1 Sungai Pagu. This research is a classroom action research where the research subjects are deaf students in class VIII and the teacher as a collaborator. The research was conducted in two cycles where the first cycle consisted of four meetings and the second cycle consisted of three meetings. The cycle consists of four stages, namely planning, action, observation and reflection. Data collection techniques in the form of tests and non-tests. From the results of the research, the initial ability of students, namely NA reached 30% & and AW reached 25.6%. After taking action in the first cycle, the results of the students' acquisition were 73.3% NA and 66.6% AW. After taking action in cycle II, the results of the acquisition of NA students were 93.3% and AW were 90%. The results of the data show that there is an increase in children's abilities in learning the art of plate dance using an explicit instruction.